Cystic intestinal pneumatosis revealed by peritonitis in perforated peptic ulcer: A case report - Ismael, Dandakoye Soumana; Belhaj, Anas; Sylla, Moussa; Tenkorang, Somuah; Ouadii, Mouaqit; Hassani, İbn Majdoub and Toughrai, İmane and Farih, Hassan Moulay and Mazaz, Khalid and Khalid, Ait Taleb (Journal of Surgery and Medicine, 2018)
Cystic intestinal pneumatosis is a rare condition characterized by the presence of cyst-like formations in the walls of the digestive tract. Cystic intestinal pneumatosis can affect any part of the digestive tract. However, the small and large bowels are the most affected. This pathology is more common in men and after the age of 50 years. Cystic pneumatosis of the intestines may be idiopathic or most often secondary to various diseases. The primitive forms preferentially affect the left colon with essentially submucous gaseous cysts, whereas the secondary intestinal cystic pneumatosis tend to affect the small intestines especially in the subserosa. The origin of this pathology is multifactorial but the main cause is not definitively proven. The long list of pathological associations has led to the development of various etiopathogenic theories that are not antinomic since some mechanisms may be associated. Cystic intestinal pneumatosis is most often asymptomatic and therefore fortuitously discovered. This pathology could have clinical signs like bloody and glairy stools, abdominal pain, and diarrhea. Endoscopic and radiological examinations are easy to diagnose and avoid unnecessary laparotomy explorations in benign pneumoperitoneum. Treatment varies according to its etiology. For primary forms, antibiotic therapy to reduce the hydrogen-producing colonic flora is indicated as first-line treatment. If unsuccessful, oxygen mask or hyperbaric, which will promote the replacement of hydrogen with oxygen, must be attempted. For secondary forms, the treatment is that of the causal affection. In most cases, cystic intestinal pneumatosis is asymptomatic and no treatment is needed. Surgery remains reserved for serious forms of this disease.